2011
DOI: 10.1051/0004-6361/201117755
|View full text |Cite
|
Sign up to set email alerts
|

Fossil group origins

Abstract: Context. Fossil systems are galaxy associations dominated by a relatively isolated, bright elliptical galaxy, surrounded by a group of smaller galaxies lacking L * objects. Because of this extreme environment, fossil groups (FGs) are ideal laboratories to study the mass assembly of brightest group galaxies (BGGs). Aims. We analyzed the near-infrared photometric and structural properties of a sample of 20 BGGs present in FGs in order to better understand their formation mechanisms. This represent the largest sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 88 publications
(104 reference statements)
8
53
0
Order By: Relevance
“…Such a red color was also found for NGC 6482 by Alamo-Martínez et al (2012) (g−z = 1.85 at r 50 ). Another finding of our study is the relatively low Sérsic index of n ∼ 2.82 for NGC 6482, in agreement with the studies of the FOGO group, who find Sérsic indices around n ∼ 3 for FGs (Aguerri et al 2011;Méndez-Abreu et al 2012). They argue based on Hopkins et al (2009) and Kormendy et al (2009) that low Sérsic indices for giant ellipticals (n ∼ 2.5) are tracers for dissipational mergers.…”
Section: Brightest Group Galaxysupporting
confidence: 92%
See 1 more Smart Citation
“…Such a red color was also found for NGC 6482 by Alamo-Martínez et al (2012) (g−z = 1.85 at r 50 ). Another finding of our study is the relatively low Sérsic index of n ∼ 2.82 for NGC 6482, in agreement with the studies of the FOGO group, who find Sérsic indices around n ∼ 3 for FGs (Aguerri et al 2011;Méndez-Abreu et al 2012). They argue based on Hopkins et al (2009) and Kormendy et al (2009) that low Sérsic indices for giant ellipticals (n ∼ 2.5) are tracers for dissipational mergers.…”
Section: Brightest Group Galaxysupporting
confidence: 92%
“…In particular it is smaller than reported by Alamo-Martínez et al (2012) who find values of ∼3.9 in gand z-band. However, smaller values of n for fossil group central galaxies were already reported by the FOGO collaboration (Aguerri et al 2011;Méndez-Abreu et al 2012), who obtain a mean Sérsic index of n ∼ 3 for a sample of 21 FGs.…”
Section: The Brightest Group Galaxy Ngc 6482mentioning
confidence: 74%
“…In particular, for the BGGs of our 34 FG candidates, a two-phase merger scenario was proposed to explain their scaling relations. Indeed, Méndez-Abreu et al (2012) claim that these objects went through dissipational mergers in an early stage of their evolution and assembled the bulk of their mass through subsequent dry mergers. This process seems similar to the one proposed by Díaz-Giménez et al (2008), in which the BGGs in fossil systems have undergone their last major merger later than in non-fossil systems.…”
Section: Formation Scenarios For Fossil Systemsmentioning
confidence: 99%
“…Some observations (Khosroshahi et al 2006) show that these objects are different from both isolated elliptical galaxies and central galaxies in non-fossil clusters in the sense that they have disky isophotes in the center and their luminosity correlates with velocity dispersion, while other authors (La Barbera et al 2009;Méndez-Abreu et al 2012) found no differences in isophotal shapes between fossil and non-fossil central galaxies. In Méndez-Abreu et al (2012) we analyzed deep K-band images of 20 BGGs in fossil and non-fossil systems and showed that these galaxies follow the tilted fundamental plane of normal ellipticals (see Bernardi et al 2011). This suggests that BGGs are dynamically relaxed systems that suffer dissipational mergers during their formation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation